Análise da estabilidade de cor de botões de íris artificiais obtidos por diferentes técnicas e após o envelhecimento acelerado - Bannwart, Lisiane Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
As próteses oculares são responsáveis pela recuperação da estética e auto-estima do usuário. As técnicas existentes para a confecção da prótese ocular devem resultar em íris artificiais perfeitamente estéticas com conseqüente dissimulação do defeito facial. Dessa forma, este estudo tem como propósito verificar a alteração de cor do botão de íris artificial entre diferentes técnicas após a polimerização e o envelhecimento acelerado. Foram confeccionadas 60 amostras simulando próteses oculares distribuídas em grupos (n=10) de acordo com a técnica utilizada, sendo: PE: técnica convencional sem verniz, PEV: técnica convencional com verniz, CA: técnica com calota pré-fabricada sem verniz, CAV: técnica com calota pré-fabricada com verniz, PI: técnica da pintura invertida sem verniz, PIV: técnica da pintura invertida com verniz. A leitura de cor foi realizada por meio de um espectrofotômetro de reflexão ultravioleta visível utilizando o sistema CIE L*a*b*, antes e após polimerização, e após 252, 504 e 1008 de envelhecimento acelerado. Os dados obtidos foram submetidos à análise de variância (ANOVA), e teste de Tukey (p<0,05). O teste de cor mostrou que após polimerização e envelhecimento acelerado todas as amostras apresentaram alteração significativa da cor, porém, as amostras com verniz protetor de tinta tiveram menor alteração em todos os períodos analisados.

Ocular prostheses are responsible not only for the recovery of aesthetic but also for the self-esteem of the anophthalmic patient. The techniques used to fabricate ocular prosthesis should result in artificial iris with adequate aesthetic and natural appearance. When such characteristics are not achieved, the fabrication of new prosthesis is indicated even in the presence of good fit of the old prosthesis. Additionally, the color instability of iris is the most relevant factor that affects the longevity of ocular prosthesis, and is related to the polymerization process of the acrylic resin and its clinical use over time. Therefore, the present study investigated the color alteration of artificial iris buttons obtained by different techniques after polymerization and accelerated aging. A total of 60 samples simulating an ocular prosthesis were fabricated and divided into groups (n=10) according to the technique used: PE – conventional technique without varnish; PEV - conventional technique with varnish; CA - Prefabricated cap technique without varnish; CAV - Prefabricated cap technique with varnished; PI - Reverse painting technique without varnish; PIV - Reverse painting technique with varnish. Color measurements were performed by using a visible ultraviolet reflection spectrophotometer with the CIE L*a*b* system, before and after polymerization, and after 252, 504 and 1008 hours of accelerated aging. Data were submitted to analysis of variance (ANOVA) and Tukey test (p<.05). After polymerization and accelerated aging periods all samples exhibited statistically color alteration; however, the varnished samples had lower color change for all periods.
Keywords: Olhos artificiais; Resinas acrilicas; Cor; Envelhecimento; Acrylic resins